Down and out or up and in? : Polarization-based measures of the middle class for Latin America - Cruces, Guillermo (2011)
This document presents a systematic review of empirical approaches to the identification and measurement of the middle class as the concept is used in the applied literature. It then presents an arguably less arbitrary definition of the middle class which is based on sound principles of distributional analysis and derived from income polarization measures. The document illustrates the differences between the existing approaches and the proposed methodology with a comparative analysis of the extent and evolution of the middle classes since the early 1990s in six Latin American countries. The polarization-based measurements of the middle class are shown to exhibit a greater degree of homogeneity in terms of some key socioeconomic characteristics than other measures employed in the literature.